Session and drill-specific physical characteristics of youth women`s football training - Harkness-Armstrong, A.; Adams, T.; Lewis, T.; Waterworth, S.; Lowry, R.; Datson, N. (Journal of Sports Sciences, 2026)
This study quantified and compared session and drill-specific physical characteristics between U10, U12, U14 and U16 youth women`s footballers. Data were collected during 80 training sessions using 10 Hz GPS, totalling 825 training observations and 2298 drill-specific observations from 116 players representing two of the English Football Association`s Emerging Talent Centres. Linear mixed modelling estimated session and drill-specific; total distance (TD), high-speed running (HSR; >3.00 m · s-1), very high-speed running (VHSR; >4.83 m · s-1) and sprinting (SPR; >5.76 m · s-1) distances (m), maximum velocity (m · s-1) and number of accelerations and decelerations (>1 m · s-2, >2 m · s-2, >3 m · s-2). During sessions, U16s covered more TD than U14s, whilst both U14s and U16s covered greater HSR, VHSR and SPR distances compared to U10s and U12s, and U10s performed more accelerations (>1 m · s-2) than U12s and U14s and more decelerations (>1 m · s-2) than all other age groups. All age groups had higher physical outputs during SSGs compared to possession and technical drills. Differences in session physical characteristics observed between age groups and between and within age groups for drill-specific physical characteristics, highlight that physical characteristics during training are age- and drill-dependent within youth women`s football. These findings have practical implications for informing coaching and talent development practices within youth women`s football.